STUDI KASUS: ANALISIS PENERAPAN TATA TERTIB KEDISIPLINAN TERHADAP SISWA SD - Imamudin, Imamudin; Purwatisari, Ani; Ningsih, Puji Rahayu; Amaliah, Siti; Ramadhani, Dwi; Hidayat, Defa Luthfi (Journal of Professional Elementary Education, 2025)
The student rules above can make us aware of how important rules are, especially for the Indonesian generation. Research was conducted to analyze the influence of disciplinary regulations on students. The research method uses qualitative case studies. Research subjects were principals, teachers and 4 5th grade students. Through purposive sampling. Data collection techniques used were observation, interviews, documentation. The data analysis technique uses 4 stages of collecting data, reducing data, presenting data, drawing conclusions. The results of the research show 1) Duties and obligations, in this school you are required to arrive on time but the lack of discipline in students results in them arriving late, but they are not immediately given sanctions, they are reprimanded first or asked what the problem is that causes lateness. 2) Prohibition for students, when they break the rules, such as throwing rubbish carelessly during breaks when leaving their seats, rubbish lying around, then the teacher will automatically monitor who is sitting here, then the children will be called for discipline. 3) Sanctions are binding, no one violates them and is worried, let alone calling their parents, there are some children who break the rules but can still be handled by the teacher.